Palaeobiology of latest Ediacaran phosphorites from the upper Khesen Formation, Khuvsgul Group, northern Mongolia - Anderson, R; McMahon, S; Macdonald, F; Jones, D; Briggs, D (Taylor and Francis, 2018)
Microfossil assemblages that include large acritarchs with complex processes, known as Doushantuo-Pertatataka-type acritarchs, are recovered from early Ediacaran successions globally. They are commonly found in shale and chert lithologies, but their diversity and palaeobiological significance is greatest when they are phosphatized. The best-known examples are from the Doushantuo Formation, South China, which preserves over 60 taxa including possible embryonic forms which may represent the oldest fossil animals. Fossils have only been recorded in four Ediacaran phosphorite deposits. Here we report the fifth such occurrence, from phosphorites of the upper Khesen Formation, Khuvsgul Group, northern Mongolia, where preservation rivals that in the Doushantuo Formation. The assemblage includes the likely cyanobacteria Obruchevella delicata, O. magna, O. parvissima and O. valdaica, as well as various Siphonophycus filaments, the possible alga Archaeophycus yunnanensis, and the Doushantuo-Pertatataka-type acritarchs Appendisphaera grandis, A. fragilis, A. tenuis, Cavaspina basiconica, Variomargosphaeridium gracile and V. aculeiparvum, sp. nov. The phosphorites also preserve the multicellular embryo-like taxon Megasphaera, which is represented by M. minuscula sp. nov. and potentially by M. puncticulosa. Geological and chemostratigraphical data suggest a latest Ediacaran age for the Khesen assemblage, immediately prior to the Proterozoic–Phanerozoic boundary. Thus, this is the youngest Doushantuo-Pertatataka-type microfossil assemblage yet described. It extends the range of Appendisphaera, Cavaspina, Megasphaera and Variomargosphaeridium upward by tens of millions of years. The assemblage adds to a growing database of Ediacaran fossils and emphasizes the importance of Mongolian strata to understanding the transition from a broadly microbial Proterozoic Eon to a Phanerozoic Eon where macroscopic animals acted as geobiological agents.